Penerapan Bahasa Indonesia Baku dalam Mempelajari Biologi di Tingkat Universitas : Studi Kasus di Universitas Negeri Medan - Sinaga, Yefta Darniati; Sitanggang, Widya Purnama; Aritonang, Putri Ayu; Wulandari, Syahfitri; Febriana, Ika (Jurnal Ilmu Sosial, Humaniora dan Seni, 2024)
This study aims to explore the implementation of standard Indonesian language in biology learning at the university level. The use of standard language plays a crucial role in building a strong academic foundation, enhancing scientific communication skills, and maintaining the quality of the teaching and learning process. However, its implementation often faces challenges such as students' diverse language backgrounds, perceptions of the formality of standard language, lack of emphasis from educational institutions, and limited resources and instructional materials supporting its use. Using a qualitative approach, this research involves interviews with students, lecturers, and language experts, as well as direct observation of biology lectures. The findings reveal that the use of standard Indonesian language in biology learning can help students better understand abstract concepts and specific terminologies, as well as improve their ability to effectively communicate findings and research results. Nevertheless, various challenges as mentioned above hinder its consistent application. This study provides new insights into the importance of using standard language in academic contexts and identifies effective strategies to enhance its implementation in biology learning at the university level.